2010
DOI: 10.1177/0040517510371861
|View full text |Cite
|
Sign up to set email alerts
|

Decision Fusion for Visual Inspection of Textiles

Abstract: Automated Visual Inspection (AVI) is the process of detecting, analyzing and classifying abnormal structures in a surface using machine vision techniques. The increasing competition in the industrial sector imposes high requirements on controlling the quality of flat surface products such as textiles, paper, steel slabs, glass, plastic films, foils, parquet slabs, ceramics etc. Automation of the visual inspection process saves companies a lot of time and raises the quality of their products by avoiding the sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
(64 reference statements)
0
6
0
Order By: Relevance
“…The fusion procedure for multiple classifiers [56][57][58] being considered here is illustrated schematically in Figure 2, using the hidden Markov (HMM), Bayesian rule, Gaussian mixture (GMM), and K-means models [59,60].…”
Section: Multi-classifier Fusionmentioning
confidence: 99%
See 1 more Smart Citation
“…The fusion procedure for multiple classifiers [56][57][58] being considered here is illustrated schematically in Figure 2, using the hidden Markov (HMM), Bayesian rule, Gaussian mixture (GMM), and K-means models [59,60].…”
Section: Multi-classifier Fusionmentioning
confidence: 99%
“…Since individual classifiers perform differently, depending on the type of application, the use of multiple classifiers has been investigated in some fields for making monitoring systems more robust [16][17][18][19][20][21][22]. Conceptually, this is similar to sensor fusion which capitalizes on the advantages of individual sensors and reduces sensitivity to noise [8,[23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Hence automatic defect identification, with the help of digital image proceesing scheme, is a natural alternative. In this direction, defect detection in application areas such as automated manufacturing [2,3], textile fabric [4][5][6][7][8][9][10][11], film industry [12][13][14], wood [15][16][17], construction industry [18], Printed Circuit Board (PCB) ( [19][20][21], wafer [22][23][24][25], solar cells [25][26][27][28], paper industry [29], leather [30], food processing [31,32], and rails [33] are reported in the literature. These image analysis techniques, designed for defect detection, are implemented either on non-textured surface like paper and glass materials or homogeneously textured surfaces like textile or on structural patterns like semiconductor wafer dies and Liquid Crystal Display (LCD).…”
Section: Literature Surveymentioning
confidence: 99%
“…Different approaches give different results that contribute to greater diversity of results and combinations of them will lead to better results than any individual approach. Tolba et al 17 presented a multi-classifier decision fusion technique based on majority voting to solve the problems of sensitivity to parameter variation and to make use of the advantages of the individual feature sets for accurate texture characterization. Mahajan et al 18 have concluded that the contextual-analysis-based defect-detection approaches are more promising than filter-based decomposition approaches.…”
Section: Overview Of Defect Detection Approachesmentioning
confidence: 99%